(untitled) - Lewis, Ricki (Boston, MA, 2005)
The goal of this Case Workbook is to place the information in Human Genetics: Concepts and Applications into real context. Most of the cases come from the medical or scientific literature, with an emphasis on the unusual. Many introduce information and details that are not found in textbooks. Each case includes information, Online Mendelian Inheritance in Man number, if it concerns a single gene disorder, and questions. The cases are organized to follow the chapter outline of the textbook. They are followed by a large section of "Connections and Synthesis" questions that draw from several parts of the textbook and are an excellent tool to study for a final exam.
Keywords: Human genetics; Handbooks, manuals, etc